Oxygen consumption in fry and fingerling stages of Indian major carps analysed using indigenously developed respirometer - Mohapatra, B. C.; Das, L.; Mahanta, S. K.; Sahu, H.; Sahoo, P.; Lenka, S.; Anantharaja, K. (Indian Journal of Fisheries, 2017)
Experiments were conducted under laboratory conditions for determination of oxygen consumption of advanced fry, fingerlings and advanced fingerlings of Indian major carps, catla Catla catla (Hamilton, 1822); rohu Labeo rohitaÂ (Hamilton, 1822); and mrigal Cirrhinus mrigala (Hamilton, 1822) in freshwater medium of total alkalinity varying between 150-154 mg l-1, total hardness 130-140 mg l-1, pH 7.5-8.0, carbon dioxide 5.6-12.0 mg l-1 and temperature 31-35oC. Experiments were conducted in acrylic respirometers designed and developed for this purpose. The oxygen consumption values for advanced fry, fingerlings and advanced fingerlings of catla were 634Â±9, 565Â±27 and 516Â±28; rohu 549Â±26, 459Â±41 and 374Â±38 and mrigal 532Â±24, 449Â±28 and 343Â±30 mg kg body wt-1 h-1 respectively. In all stages, oxygen consumption values of catla varied significantly (p<0.05) from rohu and mrigal, whereas no significant differences were noticed between rohu and mrigal. Oxygen consumption was found to be more in all the three developmental stages of catla compared to corresponding stages of rohu and mrigal. In all the fishes, oxygen consumption was found to be higher in advanced fry stage than fingerling and advanced fingerling stages. The lower critical tolerance limits of oxygen in water for survival of advanced fingerlings of catla, rohu and mrigal were found to be 0.4, 0.32 and 0.32 mg l-1 respectively.